2017
DOI: 10.1099/jmm.0.000440
|View full text |Cite
|
Sign up to set email alerts
|

Rv1458c: a new diagnostic marker for identification of Mycobacterium tuberculosis complex in a novel duplex PCR assay

Abstract: The duplex PCR assay could be developed for use as a screening test to identify MTBC in clinical specimens in peripheral laboratories with limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The identification of genes that do not show any SNV in a large number of global clinical isolates (invariant regions), would be potential diagnostic markers for identification of M. tuberculosis complex [ 30 – 32 ]. We found several invariant genes in 1553 global clinical isolate including VPCI591.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of genes that do not show any SNV in a large number of global clinical isolates (invariant regions), would be potential diagnostic markers for identification of M. tuberculosis complex [ 30 – 32 ]. We found several invariant genes in 1553 global clinical isolate including VPCI591.…”
Section: Discussionmentioning
confidence: 99%
“…We found several invariant genes in 1553 global clinical isolate including VPCI591. It has been shown that the invariant region in 190 bp region of Rv1458c and partial regions of Rv0440 can be used as diagnostic markers for the identification of M. tuberculosis complex (MTBC) [ 30 ]. The major group of invariant genes in our study includes, toxin antitoxin pathway genes like Rv0661c , Rv2760c , Rv0664 , and Rv0581 , and transposase of IS elements (Insertion elements) like IS6110 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of genes that do not show any SNV in a large number of global clinical isolates (invariant regions), would be potential diagnostic markers for identification of M.tuberculosis complex (51-53). We found several invariant genes in 1553 global clinical isolate including VPCI591.…”
Section: Discussionmentioning
confidence: 99%
“…We found several invariant genes in 1553 global clinical isolate including VPCI591. It has been shown that the invariant region in 190bp region of Rv1458c and partial regions of Rv0440 can be used as diagnostic markers for identification of M.tuberculosis complex (MTBC)(51). The major group of invariant genes in our study includes, toxin antitoxin pathway genes like Rv0661c, Rv2760c, Rv0664 , and Rv0581 , and transposase of IS elements (Insertion elements) like IS6110 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sensitivity of LAM assay differs significantly between varying health settings. [3][4][5][6] In sub-Saharan Africa, 32% of the global TB burden is found in patients co-infected with HIV/AIDS, whereas in South-East Asia this figure…”
Section: Introductionmentioning
confidence: 99%